Mga Bintana ng Liwanag sa Hilaga - Brugada, Kristoffer (Archīum Ateneo, 2024)
Writing as an award-winning documentary producer and writer for television, Kristoffer Brugada considers Rays of the Invisible Light as a needed opportunity to hear what young Moro writers from the South feel about their own culture. In particular, Brugada lauds their attempt to give an unflinching look at local practices that outsiders may regard as politically incorrect, like the keeping of household slaves or suguon. Brugada also admires the authors’ complex treatment of issues in cases where Moros themselves reject tradition, like pork intake which is considered Haram or unclean. Although Brugada feels that the contributions are uneven in style and complexity, he nonetheless welcomes the rare opportunity to hear from a sector that is often marginalized in Philippine society.